The miracle jar : a Hanukkah story - Penn, Audrey, 1947- (Tanglewood Press, 2008)
A family in the Old Country hopes to recreate the miracle of the first Hanukkah by making a small jar of cooking oil last long enough to make a treat for each of the eight nights.